Compassion fatigue, compassion satisfaction and work engagement in residential child care - Kerry Audin; Jolanta Burke; Itai Ivtzan (Scottish Journal of Residential Child Care)
Due to the challenging nature of the setting, residential childcare staff are at risk of developing compassion fatigue, including burnout and secondary traumatic stress. There is also opportunity to experience compassion satisfaction from supporting young people in need. These concepts are under-researched in residential childcare, as is work engagement; a sense of vigour, dedication and absorption at work which is beneficial for employees and organisations. This quantitative study investigated the relationship between compassion fatigue, compassion satisfaction and work engagement in staff working in independent residential childcare organisations in England, Scotland and Wales. The study used a within-participants design using correlational analyses, with a sample of 100 participants who completed a self-report questionnaire. Work engagement was positively correlated with compassion satisfaction and negatively correlated with the burnout aspect of compassion fatigue but not secondary traumatic stress. However, the absorption component of work engagement was positively associated with secondary traumatic stress, reflecting that burnout and secondary trauma are distinct aspects of compassion fatigue that relate differently with work engagement. It is recommended that residential childcare organisations be aware of, and implement support structures to prevent or minimise, both burnout and secondary traumatic stress in their employees.